Conceptualizing the Social and Political Context of the Health Workforce: Health Professions, the State, and Its Gender Dimensions - Bourgeault, Ivy Lynn (Frontiers in Sociology, 2017)
This paper attempts to address the theoretical vacuum that exists within the growing literature on the sufficiency and stability of the health workforce that has dominated health policy agendas worldwide. Conceptualizing the context of the health workforce, and the relationship between health professions and the state more specifically, draws upon critical areas of social theory and health. The sociology of professions literature, and its focus on professional projects, point to the important role that the state plays as an audience for social closure strategies. Depicting the state in this manner, however, does not enable us to explain why some state-directed strategies are successful whereas others are not. An expanded analysis of the state, its interests and the efficacy of the strategies directed towards it is augmented with reference to health policy literature. I present a model which attempts to integrate the conceptualization of the state in the professions and policy literatures as a means to better understand the context of the relations between the state and the health profession. The specific gender dimensions of this relationship are then explored through a consideration of female health professional projects and the role of women vis-a-vis the state.